On Problem of “Relict” Phenomena in American English Grammar - N. N. Goncharova (Научный диалог)
The article considers the most frequently mentioned relic phenomena in the grammar of the American English language, in particular, the morphology of non-standard verbs (the use of participles gotten and proven , that lost the suffix - en in the British English, and regularization of the past tense and participle II of the verbs such as burn , lean , spell ); the use of synthetic forms of subjunctive mood and congruence of a verb-predicate in the singular with the subject, expressed by a collective name. It is shown that, according to modern research, these grammatical phenomena should be attributed to the number of examples of “colonial revival”, not “colonial backlog.” For example, the participle gotten and synthetic form of the subjunctive mood in the 18th-19th centuries were rarely used; standard forms of verbs such as burn , lean , spell in American literary texts of the 18th century were less common than in English literary texts. Currently, these phenomena are approved as normal. Congruence of a verb-predicate in the singular with a subject, expressed by a collective name, was peculiar to both the American and British English in the early stages of their development. There is a tendency to borrow these grammatical phenomena in the British English.